2019
DOI: 10.2174/1871530319666190111121913
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Patients with Diabetic Foot Ulcer: Effects on Diabetic Microvascular Complications and Related Conditions

Abstract: Objective: We aimed to investigate the etiology and prevalence of anemia in patients with diabetic foot ulcers and the relationship between both microvascular complications and related conditions and anemia. Methods: We retrospectively collected and evaluated the data of 225 patients with diabetic foot ulcer followed at our clinic. The demographic characteristics of the patients were analyzed. Complete blood count for those with anemia, serum iron, iron-binding capacity, ferritin, transferrin saturation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In recent studies, anemia has been demonstrated to be prevalent in patients with DM, especially in the setting of DFUs [ 39 , 40 , 41 , 42 , 43 , 44 ]. However, there are conflicting reports on the correlation between anemia and DFU prognosis.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…In recent studies, anemia has been demonstrated to be prevalent in patients with DM, especially in the setting of DFUs [ 39 , 40 , 41 , 42 , 43 , 44 ]. However, there are conflicting reports on the correlation between anemia and DFU prognosis.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…The estimated glomerular filtration rate (GFR) (in mL/min/1.73 m 2 ) was calculated according to the Chronic Kidney Disease Epidemiology Collaboration equation. 17 The microalbuminuria level (in mg/dL) was assessed using a 50 mL midstream urine sample.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic nonhealing skin ulcers, especially diabetic foot ulcers (DFUs), are one of the most serious complications associated with DM. In recent decades, studies of the pathophysiology of DFUs have demonstrated that impaired angiogenesis plays a pivotal role in the development of DFUs by delaying wound healing [3][4][5] . Angiogenesis, which is the formation of new blood vessels, occurs as early as Day 3 after wounding.…”
Section: Introductionmentioning
confidence: 99%